A dedicated control design methodology for improved tilting train performance - Magalhães, Hugo (2021)
The development of detailed multibody models of railway vehicles is essential to address industrial problems through computational tools. The assessment of vehicle dynamic performance is one of the studies that can be performed with a multibody software. But when tilting trains are considered, which comprise active suspension elements, control engineering theories are required to estimate the forces developed by the actuators. Despite its importance, in general the details about the tilting control algorithm are unknown. In this work, a dedicated control design methodology is proposed to estimate the control algorithm of a tilting system in order to assure a proper vehicle performance. For this purpose, a detailed multibody model of a tilting train is used to perform a batch of simulations in order to develop an accurate linear model of the tilting system and to study its performance in realistic operation conditions. Thus, the traditional control techniques can be used to assess the tilting system dynamics and to design the control algorithm so that proper tilting performance is ensured. The control algorithm and the tilting performance are tested on a curved and tangent track with track irregularities. The comfort indexes PCT and RMS are used here to assess the tilting system.